The Influence of Village Council Oversight on Government Performance through the Village Financial System - Rina Kusrini; Fanlia Prima Jaya (P3M Politeknik Negeri Banjarmasin, 2024)
The objective of this study is to determine whether internal supervision by the Village Council influences the performance of village governments, whether internal supervision by the Village Council affects the use of the village financial system, and whether internal supervision by the Village Council impacts village government performance through the use of the village financial system. The analysis method used in this study includes hypothesis testing based on the results of the inner structural model testing, which includes R-Square output, parameter coefficients, and t-statistics with total sample of 100 Village Council members. Based on the research findings, it is evident that internal supervision by the Village Council does not directly influence village government performance. However, internal supervision by the Village Council does affect the use of the village financial system, and internal supervision by the Village Council influences village government performance indirectly through the use of the village financial system.